Research on the Planning and Construction of National Industrial Metrology Center Park: -- Taking Shandong Province as an Example - Shang, Jiankang; Zhang, Zheng; Niu, Zhao; Wang, Yongcai; Zhou, Yunteng; Yin, Fuli (Transactions on Economics, Business and Management Research, 2024)
Metrology refers to the activity of achieving unified physical and chemical units and ensuring accurate and reliable measurement values.In the field of metrology, we have always adhered to the principle that “Only accurate measurement can make perfect measurement”, and have clearly defined the important role of metrology in the manufacturing industry, then take “Only to create a fine, can be accurately measured” as the standard, the dialectical unity between the two. Different from the general sense of industrial architecture, the core task of industrial metrology park is “To build houses for precision equipment, to build laboratories for metrologists”, this has put forward many new requirements to the capital construction work from the planning, the design to the construction. With the successful acceptance of the park and put into use, this paper reviews and combs the construction process from the point of view of the pre-planning and design of the park, and puts forward a Shandong model for reference for the construction of similar projects.